The Effect of Hr Information System on The Performance of STIE Trisna Negara Employees - Garaika Garaika; Helisia Margahana (International Journal of Artificial Intelligence Research, 2022)
Broadly speaking, the purpose of this study is to determine the HR information system and employee performance at PT. Rabbani, and to find out how much influence the HR information system has on employee performance at STIE Trisna Negara. This research was conducted at STIE Trisna Negara, to find out the causes of the downward trend in employee performance. This is thought to be caused by problems with the HR information system, resulting in decreased employee performance. The research method used is an exploratory survey method using SEM-PLS Structural Equaltion Modeling. The sample in the study was 36 employees. The results of this study indicate that the HR information system has an effect on employee performance. Thus, the conclusions that can be drawn from this study are that: to increase the influence of the HR information system on employee performance, by following all the Company's Operational Standards by taking into account the stages that have been imposed by the company.